The Photochemistry Of Cr(Co)6 In High Pressure Low Temperature Polymer Matrix Monitored By Fourier Transform Infrared And Uv-Vis Spectroscopy - Harun, FW (Penerbit Utm Press, 2024)
The aim of this work is to develop a new type of polymer matrix which can be used to study the reactive intermediates produced from UV photolysis of metal carbonyl complexes measured with FTIR as well as UV-vis spectroscopy. The photochemistry of Cr(CO)(6) impregnated in Teflon-AF polymer with the presence of N-2, CH4 and even weak ligand i. e. Xe and He were conducted at extremely low temperature. Photolysis of Cr(CO)(6) under N2 environment produces up to four carbonyl groups being replaced with the N2. Meanwhile, the photochemistry of Cr(CO)(6) under Xe and CH4 produce the reactive complexes of Cr(CO)(5)(Xe) and Cr(CO)(5)(CH4) respectively. Teflon-AF was found to be the suitable matrix material as the -C-F-bond binds very weakly to the metal center.